Reversing Democracy: Examining the Nagari Institution in West Sumatra, Indonesia - Valentina, Tengku Rika; Putera, Roni Ekha; Irawati, Irawati (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2019)
Democracy consolidation is a process that reduces the possibility of reversing democratization, for the process is featured by negotiations among actors that wants to "promote" the new system or "rules of the game" rather than to damage the old system, and everything is reflected in the process of returning to the nagari in West Sumatra, Indonesia. There is an anomaly of power when the nature of state authority finally raises a "drama" of a political system directly applied to local nagari institutions. The renewal of nagari from previously imposed uniformity under the Village Government Law 5/1979 cannot be analyzed merely as an issue of autonomy and governance. It must be understood within regulative, normative, and cultural orders that shape institutions and their actors. This study adopts a sociological and historical analysis of neo-institutionalism to examine the political dynamics of nagari. The key problem discussed in this article is how institutional structures, rules, norms, and cultures affect local elites and communities during the consolidation of local democracy in nagari in West Sumatra. A post-positivist explorative method is applied as a tool to dissect and analyze problems with the aims to yield solid, conceptual, and varied findings and data analysis. Analysis and discussion are directed to two findings: first, traditional and modern nagari government institutions; second, consolidation process of nagari institutions in West Sumatra. Overall, the analysis and discussion of the political and governance system of traditional and modern nagari become an interesting object study to thoroughly examine the local democracy consolidation journey occurring in West Sumatra.